Examining the Influence of Women's Leadership and Flexible Working Arrangements on Employee Performance Across Generations in Startups - Desi Prabandari Kusuma Ningtyas; Sukmawati, Anggraini; Sartono, Bagus (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
Startups, as rapidly growing and dynamic organizations, face unique challenges in managing human resources, especially regarding generational diversity and the need for work flexibility. In this regard, the adoption of flexible working arrangements and women’s leadership are crucial elements thought to enhance employee performance. This study collected data through a questionnaire with 140 respondents. A quantitative method with descriptive analysis was used to depict the questionnaire data filled out by respondents and Structural Equation Modelling (SEM-PLS) was applied to analyse the relationships among the variables studied. This research examines the influence of women’s leadership and flexible working arrangements on employee performance while positioning a multigenerational workforce as a moderating factor within the proposed relationships. The results demonstrate that both women’s leadership and flexible working arrangements (FWA) each exert a positive influence on employee performance. Multigenerational does not moderate the relationship between women’s leadership and performance, indicating that leadership qualities such as inclusiveness, empathy and collaboration are broadly valued across generations. In contrast, multigenerational moderates flexible working arrangements on employee performance, highlighting the role of work flexibility in accommodating differing expectations and work preferences among employees from various generational backgrounds.